Applications of Nanoparticles in Magnetic Resonance Imaging: A Comprehensive Review - Asl, Halime Mansoury (Asian Journal of Pharmaceutics (AJP), 2017)
Technology advancements in synthesis and modification of nanoscale materials have advanced the development of different medical applications. Nanoparticles (NPs) have demonstrated promising potentials in diagnostic medicine especially for magnetic resonance imaging (MRI). Iron oxide, gold, and gadolinium NPs have been used in preclinical and clinical studies as contrast enhancing agents. Studies are ongoing to find the optimum parameters of these NPs as contrast agents (CAs) of MRI. This study aims to review the recent applications of iron oxide, gold, and gadolinium NPs as contrast enhancing agents in MRI for diagnosis of different disorders. The databases of PubMed (1980-2016), Web of Science (1980-2016), Scopus (1980-2016), and Google Scholar (1980-2016) were explored using the search terms â€œNanoparticles,â€ â€œContrast agents,â€ â€œMagnetic Resonance Imagingâ€ and â€œdisease.â€ The obtained results were screened for the title and abstract and comprehensively reviewed. MRI CAs are divided into T1 and T2 CAs, respectively, used for T1 and T2 weighted protocols in MRI. Iron oxide, gadolinium, and gold NPs are the most common CAs used in MRI. High magnetization values, small size, narrow particle size distribution are the main features of NPs as CAs in MRI. Gadolinium is the most common T1 CAs used in MRI. However, it is associated with toxicity which is a serious concern in patients with renal failure. Iron oxide NPs can be used for these patients. However, the main limitation of iron oxide NPs is limited relaxivity. The relaxivity strongly depends on the size of NP. Paramagnetic NPs serve as T1 CAs and super paramagnetic NPs as T2 CAs. Modulating the size of NPs is the main parameter to adjust different NPs for different MRI protocols. Recent years to overcome the problem of gadolinium and iron oxide NPs, different paramagnetic and super paramagnetic NPs are developed.